SPECTRUM OF INTESTINAL COCCIDIAN PARASITES AMONG HIV PATIENTS ATTENDING A TERTIARY CARE HOSPITAL IN NORTH INDIA - HARIPRIYA BANSAL; SAPNA BATRA; LOVEENA OBEROI; ANURADHA MALHOTRA; KAMALDEEP SINGH; BABICA MOHINDROO (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Human immunodeficiency virus (HIV) infection severely compromises the immune system, leading to increased susceptibility to opportunistic infections. Intestinal parasitic infections, particularly those caused by coccidian parasites, significantly contribute to morbidity and mortality in HIV-infected individuals, with diarrhea being one of the most common clinical manifestations. Methods: The study involved HIV seropositive and seronegative patients presenting with diarrhea and other gastrointestinal symptoms. Stool samples were analyzed using direct wet mount preparations and modified acid-fast staining to identify various intestinal coccidian parasites among HIV patients and their prevalence. Results: Among 207 HIV seropositive patients tested, 62% were male, with ages ranging from 11 to 60 years. Cryptosporidium was the only coccidian parasite detected in our study, with a higher prevalence (77%) in patients with chronic diarrhea compared to those with acute diarrhea (23%). A significant majority of parasites were found in patients with cluster of differentiation (CD) CD4 counts below 200/mm³. Conclusion: There is a high prevalence of intestinal coccidian parasites among the studied population. Health education targeted at both HIV patients and community health workers regarding potential sources and transmission routes of these infections is crucial to reduce contamination and promote patient health and longevity.